2002
DOI: 10.1038/sj.ijo.0802058
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged adaptation to fat-rich diet and training; effects on body fat stores and insulin resistance in man

Abstract: OBJECTIVE:To investigate the effect of prolonged adaptation to training and fat-or carbohydrate-rich diet on body composition and insulin resistance. DESIGN: Longitudinal study. Of three groups two consumed a fat-rich diet, of which one performed regular training (FAT-Train, n ¼ 17) and the other maintained normal habitual activity (Fat-Control, n ¼ 8). The third group trained and consumed a carbohydrate-rich diet (CHO-Train, n ¼ 16). SUBJECTS: Forty-one untrained, healthy male subjects. MEASUREMENTS: Before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…A carbohydrate-enriched diet has been shown to induce insulin resistance and hyperinsulinemia, which in turn is associated with elevated blood pressure and initiation of a complex biochemical cascade that leads to vascular cell damage. 5,6 Oral administration of resveratrol was shown to inhibit insulin sensitivity and to reduce the body weight of mice fed on high-fat diet. 7 Most of the effects of resveratrol on lifespan in lower life forms are thought to be mediated by the deacetylase sir-2, a member of the conserved sirtuin family of proteins.…”
mentioning
confidence: 99%
“…A carbohydrate-enriched diet has been shown to induce insulin resistance and hyperinsulinemia, which in turn is associated with elevated blood pressure and initiation of a complex biochemical cascade that leads to vascular cell damage. 5,6 Oral administration of resveratrol was shown to inhibit insulin sensitivity and to reduce the body weight of mice fed on high-fat diet. 7 Most of the effects of resveratrol on lifespan in lower life forms are thought to be mediated by the deacetylase sir-2, a member of the conserved sirtuin family of proteins.…”
mentioning
confidence: 99%
“…Four randomised controlled trials were identified that presented evidence on diets differing in the proportion of carbohydrate to fat or protein in relation to blood glucose response two hours after an oral glucose tolerance test (Swinburn et al, 2001;Lasker et al, 2008;Due et al, 2008a). No further trials were identified in the update search (Cardio-metabolic review, diabetes chapter p185) (Racette et al, 1995;Golay et al, 1996;Golay et al, 2000;Swinburn et al, 2001;Helge, 2002;Colette et al, 2003;Landry et al, 2003;Lovejoy et al, 2003;Wolever & Mehling, 2003;Clifton et al, 2004;Segal-Isaacson et al, 2004;Dansinger et al, 2005;Lofgren et al, 2005;Raatz et al, 2005;Petersen et al, 2006;Howard et al, 2006b;Ebbeling et al, 2007;Gardner et al, 2007;Maki et al, 2007b;Phillips et al, 2008;Due et al, 2008a;Frisch et al, 2009;Grau et al, 2009;Kirk et al, 2009;Morgan et al, 2009;Sacks et al, 2009). Five trials were subsequently identified in the update search (Goree et al, 2011;Haufe et al, 2011;Shikany et al, 2011;Tierney et al, 2011;Brooking et al, 2012 Nearly all trials employ energy restricted weight loss diets that vary both carbohydrate (between 5% and 65% energy) and fat (between 18% and 40% energy) between groups.…”
Section: Cohort Studiesmentioning
confidence: 99%
“…Thirteen randomised controlled trials were identified that presented evidence on diets differing in the proportion of carbohydrate to fat on measures of insulin resistance/sensitivity (Helge, 2002;Wolever & Mehling, 2002;Foster et al, 2003;Lofgren et al, 2005;Raatz et al, 2005;Johnston et al, 2006;Maki et al, 2007b;Tinker et al, 2008;Due et al, 2008a;Grau et al, 2009;Kirk et al, 2009;Sacks et al, 2009;de Luis et al, 2009a). Five trials were subsequently identified in the update search Goree et al, 2011;Haufe et al, 2011;Shikany et al, 2011;Tierney et al, 2011) 5.105.…”
Section: Insulin Resistance/sensitivitymentioning
confidence: 99%
See 2 more Smart Citations